Wyniki badań na osadzie kultury pucharów lejkowatych na stanowisku nr 4 w Mierzynie, gm. Dobra Szczecińska i ich znaczenie dla wiedzy o środkowym neolicie Dolnego Nadodrza - Dziewanowski, Marcin; Pyżewicz, Katarzyna (Folia Praehistorica Posnaniensia, 2016)
This paper presents the results of analyses of materials recovered during 2004 rescue excavations of a Funnel Beaker Culture (TRB) dwelling pit at Mierzyn, site 4. It provides a detailed and multifaceted analysis of the archaeological record and attempts to assess the significance of the find for the studies on the Middle Neolithic in the Lower Oder region. The article contains a detailed description of selected archival finds from the area occupied by the site and discusses their previous interpretations.